The m6A methylation profiles of immune cells in type 1 diabetes mellitus - Wang, Yimeng; Xu, Linling; Luo, Shuoming; Sun, Xiaoxiao; Li, Jiaqi; Pang, Haipeng; Zhou, Jun; Zhou, Yuemin; Shi, Xiajie; Li, Xia; Huang, Gan; Xie, Zhiguo; et al. (Frontiers in Immunology, 2022)
Background Type 1 diabetes mellitus (T1DM) is caused by immune cell-mediated β-cell dysfunction. In recent decades, N6-methyladenosine (m6A) has attracted widespread attention in the scientific research field because it plays vital roles in the pathogenesis of immunity-related diseases, including autoimmune diseases. However, neither the m6A modification profile nor the potential role it plays in T1DM pathogenesis has been investigated to date. Materials and Methods An m6A mRNA epitranscriptomic microarray analysis was performed to analyze m6A regulator expression patterns and m6A methylation patterns in immune cells of T1DM patients (n=6) and healthy individuals (n=6). A bioinformatics analysis was subsequently performed to explore the potential biological functions and signaling pathways underlying T1DM pathogenesis. Furthermore, mRNA expression and m6A methylation levels were subsequently verified by qRT–PCR and methylated RNA immunoprecipitation–qPCR (MeRIP–qPCR), respectively, in the T1DM and healthy groups (n=6 per group). Results Among the multiple m6A regulators, METTL3 and IGF2BP2 had significantly downregulated expression, and YTHDC1 and HNRNPA2B1 had significantly upregulated expression in the T1DM group relative to the healthy group. The microarray analysis revealed 4247 differentially methylated transcripts, including 932 hypermethylated and 3315 hypomethylated transcripts, and 4264 differentially expressed transcripts, including 1818 upregulated transcripts and 2446 downregulated transcripts in the T1DM group relative to the healthy group. An association analysis between methylation and gene expression demonstrated that the expression of 590 hypermethylated transcripts was upregulated, and that of 1890 hypomethylated transcripts was downregulated. Pearson correlation analysis showed significant correlations between the expression levels of differentially expressed m6A regulators and the methylation levels of differentially methylated transcripts and significant correlations between the expression levels of differentially expressed m6A regulators and that of differentially expressed transcripts. Moreover, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses demonstrated that differentially methylated transcripts were involved in pathways related to immunity, including some closely associated with T1DM. Conclusions Our study presents m6A regulator expression patterns and m6A methylation patterns of immune cells in T1DM, showing that the m6A mark and m6A regulators are promising targets for T1DM diagnosis and treatment.